Legal aspects of carbon trading Kyoto, Copenhagen, and beyond - Freestone, David; Streck, Charlotte (Oxford : Oxford University Press, 2009)
Since 2005 the carbon market has grown to nearly $100 billion per annum, including the EU Emissions Trading Scheme and other schemes. This work covers the legal aspects of these schemes, as well as reform of the ETS, and the successor regime to the 1997 Kyoto Protocol currently being negotiated.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Carbon offsetting -- Law and legislation